Foliar Application of Low Concentrations of Titanium Dioxide and Zinc Oxide Nanoparticles to the Common Sunflower under Field Conditions - Kolenčík, Marek; Ernst, Dávid; Urík, Martin; Ďurišová, Ľuba; Bujdoš, Marek; Šebesta, Martin; Dobročka, Edmud; Kšiňan, Samuel; Illa, Ramakanth; Qian, Yu; Feng, Huan; Černý, Ivan; et al. (Nanomaterials (Basel, Switzerland), 2020)
Nano-fertilisers have only recently been introduced to intensify plant production, and there still remains inadequate scientific knowledge on their plant-related effects. This paper therefore compares the effects of two nano-fertilisers on common sunflower production under field conditions. The benefits arising from the foliar application of micronutrient-based zinc oxide fertiliser were compared with those from the titanium dioxide plant-growth enhancer. Both the zinc oxide (ZnO) and titanium dioxide (TiO2) were delivered by foliar application in nano-size at a concentration of 2.6 mg·L-1. The foliar-applied nanoparticles (NPs) had good crystallinity and a mean size distribution under 30 nm. There were significant differences between these two experimental treatments in the leaf surfaces' trichomes diversity, ratio, width, and length at the flower-bud development stage. Somewhat surprisingly, our results established that the ZnO-NPs treatment induced generally better sunflower physiological responses, while the TiO2-NPs primarily affected quantitative and nutritional parameters such as oil content and changed sunflower physiology to early maturation. There were no differences detected in titanium or zinc translocation or accumulation in the fully ripe sunflower seeds compared to the experimental controls, and our positive results therefore encourage further nano-fertiliser research.
Keywords: nanoparticles; titanium dioxide; zinc oxide; foliar application; nano-fertilisers; sunflower